MENINGKATKAN KETERAMPILAN ABAD 21 SISWA SD DENGAN MODEL PEMBELAJARAN “KOOPERATIF THINK PAIR SHARE” BERBANTU GAMBAR ILUSTRASI - Ruswanto; Wakhudin (EDU RESEARCH, 2025)
This study aims to analyze the effect of the Think Pair Share learning model assisted by Illustrative Images on 21st-century skills. The type of research is Quasi-Experimental with One Group Pretest-Posttest design. The population of this study was fourth-grade students in Bung Tomo Sub-district Jeruklegi, Cilacap. Fourth-grade students of SDN Brebeg 01 were selected as samples in this study through a simple random sampling technique. Testing of the hypothesis using the t-test, namely paired sample t-test assisted by spss 26 application. Data on collaboration skills through observation. Critical thinking skills data were obtained through two tests, namely pretest and posttest. Testing of the research hypothesis with calculations on a Likert scale shows the assessment interval for the effect of the Think Pair Share learning model assisted by Illustrative Images on students' collaboration skills is 83.04. This proves that the average student in collaboration skills in learning change for the better. The t-test obtained a significance value of 0.00 or <0.05 which means that H0 is rejected and H1 is accepted, meaning that learning using Think Pair Share assisted by Illustrative Images has an influence on students' critical thinking skills.